2017
DOI: 10.1176/appi.neuropsych.16090171
|View full text |Cite
|
Sign up to set email alerts
|

“Top-Down” Mu-Opioid System Function in Humans: Mu-Opioid Receptors in Ventrolateral Prefrontal Cortex Mediate the Relationship Between Hedonic Tone and Executive Function in Major Depressive Disorder

Abstract: Cognitive dysfunction and anhedonia, the reduced ability to experience pleasure, are commonly comorbid symptoms that are persistent following successful resolution of negative affect in major depressive disorder (MDD). Little is known about whether they share common etiology. In the present study, the relationship between ventrolateral prefrontal cortex (VLPFC) activity, cognitive dysfunction (i.e., executive dysfunction), and positive emotionality was investigated in conjunction with mu-opioid neurotransmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…In addition, prefrontal networks involved in maintaining task-goal representations can be modulated directly via binding to its opioid receptors. In line with this suggestion, a recent PET study observed that high mu-opioid signaling (lower binding potential) in a ventral region of the lateral PFC was positively related to performance on the Wisconsin Card Sorting Test in a group of depressive patients (Light, Bieliauskas, & Zubieta, 2017). A possible mechanism at a neuronal level could be that stimulation of mu-opioid receptors suppresses interneuron spiking and increases glutamate-coded output of prefrontal neurons at multiple projection targets, which in turn might engender disorganized control and decision processes (Baldo, 2016).…”
Section: Inhibition and Effortmentioning
confidence: 69%
See 1 more Smart Citation
“…In addition, prefrontal networks involved in maintaining task-goal representations can be modulated directly via binding to its opioid receptors. In line with this suggestion, a recent PET study observed that high mu-opioid signaling (lower binding potential) in a ventral region of the lateral PFC was positively related to performance on the Wisconsin Card Sorting Test in a group of depressive patients (Light, Bieliauskas, & Zubieta, 2017). A possible mechanism at a neuronal level could be that stimulation of mu-opioid receptors suppresses interneuron spiking and increases glutamate-coded output of prefrontal neurons at multiple projection targets, which in turn might engender disorganized control and decision processes (Baldo, 2016).…”
Section: Inhibition and Effortmentioning
confidence: 69%
“…One important avenue for future research is to understand the role of mood changes in altered cognitive function. For example, studies might investigate whether endogenous variation or drug-induced changes in subjective state correlate with behavioral outcomes, as some recent work has started to do (Light et al, 2017;Weber et al, 2016). Studies investigating the effect of hedonic states on cognitive control and decision making (Dreisbach & Goschke, 2004;Isen & Means, 1983;van Steenbergen, Band, & Hommel, 2010;van Steenbergen, Band, Hommel, Rombouts, & Nieuwenhuis, 2015) could use antagonist drugs to block the opioid system to determine the role of endogenous mu-opioid neurotransmission in these effects.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…These findings suggest that these individuals are good at taking the perspective of, and reading the mental states of others. It is possible that this type of individual might also have better executive function (e.g., Light et al, 2017), which can be compromised in individuals who are clinically depressed. However, it is really unknown how these individuals function in their day-to-day lives, and these results raise important questions about the role of positive empathy in overall well-being.…”
Section: Resultsmentioning
confidence: 99%
“…It is becoming increasingly apparent that emotions and cognitive processes are closely related, and even share a common neurobiological substrate, involving the prefrontal/anterior cingulate cortex and the amygdala as well as other networks [37]. Again, while more clinical research is needed to confirm the relationship between pleasure perception and executive functioning, a recent study clearly linked increased pleasure to more efficient executive functioning in patients with major depression [38]. Intriguingly, the presence of the s-allele of the 5-HTTLPR in combination with increased childhood adversity was found to be associated with reduced executive functioning [39], thus linking together the top four levels of the translational umbrella.…”
Section: The Translational Umbrellamentioning
confidence: 99%